’N ONTLEDING VAN DIE INVLOED EN VERMOE VAN KORTAFSTANDLUGVERVOERSTEUN OP EENHEIDSTAKTIESE BEPLANNING EN OPERASIES EN AANBEVELINGS HOE HIERDIE STEUN TOT DIE MAKSIMUM BENUT KAN WORD. - Viviers, F.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
It was only as a result of the enormous technological progress in the field of arms and the development of modern tendencies in the strategy and tactics of warfare, that the influence of an efficiently co-ordinated ground - and air force on the course of a conventional war was analysed. The purpose of this article is to analyse the influence of short-distance air transport support on unit tactical planning and operations and to make recommendations for the manner in which this support may be utilized to the full.